(untitled) (Revista Brasileira de Iniciação Científica, 2022)
In the article, an investigation is present about the employer`s duties and responsibilities in regard to health and safety in the work environment in a pandemic context, in order to elucidate the peculiarities and precautions due to vulnerable groups during this extraordinary period. A bibliographical and documentary research is carried out, using the deductive approaching method. First, the work environment and its consequences on the dignity of the human person in normal times were contextualized, and then discussed about the transformations brought about by the covid-19 pandemic in that same environment. Finally, based on the regulatory frameworks and court decisions produced in Brazil amidst the pandemic until then, the duties of the employer towards occupational health and safety in this atypical scenario were addressed. It is concluded that the pandemic brings with it significant changes in labor relations, so that readjustments in health and safety methods beyond those commonly used are essential for the proper accommodation of workers, especially those who compose the so-called “risk group”, as they are particularly weakened by the pandemic impacts.